CT and MRI in the Evaluation of Thoracic Aortic Diseases - Rajiah, Prabhakar (Hindawi Publishing Corporation, 2013)
Computed tomography (CT) and magnetic resonance imaging (MRI) are the most commonly used imaging examinations to evaluate thoracic aortic diseases because of their high spatial and temporal resolutions, large fields of view, and multiplanar imaging reconstruction capabilities. CT and MRI play an important role not only in the diagnosis of thoracic aortic disease but also in the preoperative assessment and followup after treatment. In this review, the CT and MRI appearances of various acquired thoracic aortic conditions are described and illustrated.